2014
DOI: 10.1016/j.nicl.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing real time fMRI neurofeedback for therapeutic discovery and development

Abstract: While reducing the burden of brain disorders remains a top priority of organizations like the World Health Organization and National Institutes of Health, the development of novel, safe and effective treatments for brain disorders has been slow. In this paper, we describe the state of the science for an emerging technology, real time functional magnetic resonance imaging (rtfMRI) neurofeedback, in clinical neurotherapeutics. We review the scientific potential of rtfMRI and outline research strategies to optimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
175
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 113 publications
(165 reference statements)
0
175
0
Order By: Relevance
“…Of particular relevance for the application of NFT approaches in clinical practice [30, 73, 74] the present study observed that subjects were able to maintain the control over the emotion regulation pathway in the absence of feedback and for a period of at least 3 days. These findings are in line with previous studies evaluating transfer and maintenance effects of rt-fMRI NF-assisted control over regional brain activity [31, 75], and additionally suggest that successful neuromodulatory control on the pathway level can last beyond the duration of the initial training and thus transfer to contexts outside of the MRI environment.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Of particular relevance for the application of NFT approaches in clinical practice [30, 73, 74] the present study observed that subjects were able to maintain the control over the emotion regulation pathway in the absence of feedback and for a period of at least 3 days. These findings are in line with previous studies evaluating transfer and maintenance effects of rt-fMRI NF-assisted control over regional brain activity [31, 75], and additionally suggest that successful neuromodulatory control on the pathway level can last beyond the duration of the initial training and thus transfer to contexts outside of the MRI environment.…”
Section: Discussionmentioning
confidence: 76%
“…Although the crossover design with a comparably large sample (compared to previous rt-fMRI experiments, see overview [30]), inclusion of an active-control and the preregistration of the primary outcomes permitted a rigorous control for a number of potential confounds, the present findings still need to be considered in the context of some limitations. First, to allow an evaluation of the training independent of menstrual-cycle or gender effects on ER and associated neural activity [46, 47, 49], our proof-of-concept study focused on male participants.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These range from simple physical size changes of an image [11], to more advanced visualizations, such as the functional brain activation map [23], to very complex interactive virtual-reality displays [24] and even non-visual presentations, such as auditory cues [25,26]. However, to our knowledge, self-regulation across several feedback presentations within the same individuals has not been explored yet, and little is known about if and how the feedback representation affects individuals' capability to self-regulate the BOLD signal [3,5]. It has, nevertheless, been suggested that more complex feedback displays could increase a participant's cognitive load [27], taking away processing time from the task at hand: self-regulation of the brain state.…”
Section: Designmentioning
confidence: 99%
“…More recently, it has been suggested that real-time functional magnetic resonance imaging neurofeedback (rtfMRI-NF) has the potential to play an important role for therapeutic purposes [5] and the first successful clinical applications have been demonstrated, for instance, in patients with Parkinson's disease [6], depression [7], schizophrenia [8,9], spider phobia [10], chronic pain [11], chronic tinnitus [12], alcohol use disorder [13], nicotine dependence [14,15], and obesity [16]. Due to large inter-individual differences in the ability to gain conscious self-control over one's own brain signals [17,18], current research in this field is focusing on optimizing and advancing rtfMRI-NF protocols and methods.…”
Section: Introductionmentioning
confidence: 99%